High performance waterproof-breathable fully flexible tactile sensor based on piezotronics coupled OFET. (February 2023) - Yin, Ailing; Wang, Jian; Hu, Shuang; Sun, Mingyuan; Sun, Baojun; Dong, Mengwei; Zhang, Ting; Feng, Zhichao; Zhang, Haoyu; Shi, Bingqi; Zhang, Congcong; Liu, Hong
Abstract: As obtaining flexible tactile sensors with high sensitivity, waterproofness and breathability at the same time is still a huge challenge, which limits their application in advanced fields such as human prosthetics and robotic arms. Herein, a fully flexible piezoelectric tactile sensor with high-performance, energy-efficient, waterproof, and breathable was constructed by capacitive coupling the β-PVDF nanofiber membrane (NM) with electro-mechanical conversion function and organic field effect transistor (OFET) device with signal amplification function. The inherent waterproofed β-phase PVDF NM was fabricated by advanced electrospinning process, such morphology with thousands of micropores not only gives the device excellent breathability, but also increases the deformation tolerance and accelerates the respond/recovery time, so that the obtained device can be bent at will without affecting its performance. At the same time, under the guidance of pizotronics, the charge generated by PVDF membrane based on piezoelectric effect polarization was sufficient to drive the OFET device, the as-fabricated sensor shows great sensing performance in monitoring human physiological signals without applying a gate voltage. Such device exhibits excellent pressure sensitivity, detection limit, and response time of 7.94 KPa -1, 48.54 Pa and 105 ms, respectively, which may become promising device in smart electronic skins, human motion detection, and human−machine interaction. Graphical Abstract: Using natural superhydrophobic PVDF powder, the fiber interconnecting porous membrane with piezoelectric properties was obtained by advanced electrospinning process. Under the guidance of piezoelectric electronics principle, it is capacitively coupled with OFET to prepare a high performance, waterproof, breathable, energy saving fully flexible tactile sensor, which can detect human physiological signals in real time. ga1 Highlights: The natural hydrophobic characteristics of the PVDF combined with electrospinning to achieve a flexibility, waterproofness and breathability sensor. Under the guidance of piezotronics, the PVDF NM and OFET are capacitively coupled to construct a high-performance tactile sensor. The tactile sensor with high performance and comfort can realize real-time monitoring of human physiological signals.